Evaluating costs, perception, satisfaction, safety and effectiveness towards electronic cigarette at Kuantan and Pekan, Pahang, Malaysia - Aziz-ur-Rahman (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2017)
Studies are currently lacking regarding long-term effectiveness and safety of electronic cigarette (e-cig) among single users (SUs) and dual users (DUs) whom represent the real world population of vapers community. The primary outcomes of this study were complete nicotine abstinence rate and safety issues between both groups of users at week 52. The secondary outcomes were tobacco cigarette (TCG) only abstinence and ≥ 50% reduction at week 52. Users' perception, satisfaction, cost utilisation and nicotine estimation in their e-liquids were also analysed. A one year follow-up observational study was conducted among 220 regular e-cig users age >18 to 65 years from Kuantan and Pekan, Pahang, Malaysia who used e-cig for at least one month prior. The e-cig users were categorised as either SUs (used only e-cig, verified by exhaled carbon monoxide (eCO) of <8 ppm), and DUs (used both e-cig and TCG, with eCO of ≥ 8ppm). At week 52, 15.9% of SUs (n=11) vs. 6.8% of DUs (n=10) quit both TCG and e-cig, OR: 2.57; p = 0.048. Whereas 34.8% of SUs (n=24) vs. 17.1% of DUs (n=25) quit only TCG, OR: 2.58; p = 0.005. Among the DUs 23.3% (n=34) reduced ≥ 50% TCG consumptions vs. 21.7% of SUs (n=15), OR: 1.092; p = 0.863. Concerning safety issues, SUs perceived less e-cig adverse effects and withdrawal symptoms as compared to DUs. The major adverse effects and withdrawal symptoms observed between both groups were coughing, breathing problems and craving for TCG smoking. Moreover, seven possible smoking-related diseases such as COPD, angina, diabetes and two cases of hypertension were diagnosed among DUs, whereas in SUs a case of hypertension and diabetes each was detected. Analysis of 69 e-liquids by GC-MS showed high discrepancies between the label and actual nicotine concentration in more than 85% of the samples. Related to perception of e-cig use, 33% of both groups were satisfied and ranked it is an effective smoking cessation aid. Regarding e-cig cost utilisation, a total monthly average cost of MYR132.45, was spent which is less than that for conventional TCG use, reported as 178.80 MYR that calculated by the Global adult tobacco survey Malaysia (2011). The study concludes that e-cig can be used as an aid for complete nicotine abstinence among both the SUs and DUs. However, e-cig SUs are more likely to have total nicotine abstinence than DUs. Similarly, SUs are more likely to be TCG abstinent than DUs. However, e-cig is equally effective in SUs and DUs for TCG reduction. No serious adverse effects related to e-cig were detected. However, the safety of e-cig use in absolute term needs to be validated further. The nicotine analysis reveals an urgent need for manufacturing and quality standards of e-liquids in Malaysia. Both users generally have good perception and satisfaction towards e-cig after long-term use. However, more SUs had positive perception and satisfaction than DUs. Monthly cost expenditure of both the e-cig users is less as compared to TCG smokers.